5wk-3k-6k+k-10=

Simple and best practice solution for 5wk-3k-6k+k-10= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5wk-3k-6k+k-10= equation:


Simplifying
5wk + -3k + -6k + k + -10 = 0

Reorder the terms:
-10 + -3k + -6k + k + 5kw = 0

Combine like terms: -3k + -6k = -9k
-10 + -9k + k + 5kw = 0

Combine like terms: -9k + k = -8k
-10 + -8k + 5kw = 0

Solving
-10 + -8k + 5kw = 0

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '10' to each side of the equation.
-10 + -8k + 10 + 5kw = 0 + 10

Reorder the terms:
-10 + 10 + -8k + 5kw = 0 + 10

Combine like terms: -10 + 10 = 0
0 + -8k + 5kw = 0 + 10
-8k + 5kw = 0 + 10

Combine like terms: 0 + 10 = 10
-8k + 5kw = 10

Reorder the terms:
-10 + -8k + 5kw = 10 + -10

Combine like terms: 10 + -10 = 0
-10 + -8k + 5kw = 0

The solution to this equation could not be determined.

See similar equations:

| 7x+8-6x=3 | | -4+2y=3y-6 | | 22-10n+n^2=-2 | | -7m+13+8m-5= | | 7=3z+2 | | 7x+8-6x+3= | | 2y-6=11y+57 | | -22x-1x= | | (x+5)(x-9)=(2x+7)(x-5) | | ax-b=4x-7 | | .5x+.45(30)=49.5 | | -8m+15+9m=-2 | | Y=-4(4)-3 | | x-9+5x-3=5x | | 11x=10x+17 | | Y=-4(-2)-3 | | x-14.6=20 | | 5(k+2)=3(-4) | | -8m+15+9m-2= | | Y=-10(5)-3 | | n+221=333 | | 5m-13=33 | | 9x^4=3x^2-25 | | 5(5x)+12= | | 5(5x+12)= | | 4n+24=2n+42 | | 3p+5=2p+14 | | 2(13.5)+-1.5y+3y=27 | | 2*2*n*n=54 | | 12x=3x+12 | | 23xn=22135 | | 2(13.5+-1.5y)+3y=27 |

Equations solver categories